Magnetic bioactive SrFe 12O19-SiO2-CaO- Na2O-P2O5glass-ceramics for hyperthermia treatment of bone cancer - W. Leenakul (2018)
The magnetic bioglass-ceramics were introduced for hyperthermia treatment of bone cancer. The aim of this work was to study the magnetic properties of ferrimagnetic glass-ceramics from SrFe1 2 O 19 (SF)-SiO 2 -CaO-Na 2 O-P 2 O 5 system by using the modified solid-state sintering method. The results showed that sodium calcium silicate (Na 4 Ca 4 Si 6 O 18 ), strontium iron oxide (SrFe1 2 O 19 ) and iron oxide (Fe 2 O 3 ) were precipitated in all samples. The saturation magnetization (M s ), remanence (M r ) and coercivity (H c ) increased by the addition of SF in the bioglass. The samples were soaked in simulated body fluid (SBF) for 14 days in order to investigate the bioactivity of the samples in vitro. The apatite layer was found on the surface of all bioglass-ceramics confirming their biocompatibility and it increased with increasing strontium ferrite content. © 2013 Copyright Taylor and Francis Group, LLC.